Power Flow Control of Power Systems Using UPFC Based on Adaptive Neuro Fuzzy - Agus Jamal; Ramadoni Syahputra (Institut Teknologi Sepuluh Nopember, 2014)
Optimization of system capacity electric power transmission systems requires a reliable power flow controller. The power flow controllers must be able to control the level of electrical voltage and active and reactive power flow without reducing the level of stability and security of the transmission system. Latest technology in the control of power flow is a Unified Power Flow Controller (UPFC). The entire transmission line parameters are impedance, voltage, and phase angle can be controlled simultaneously by the UPFC. The method used in the conventional algorithms based UPFC is still firmly with logic. These algorithms have difficulties to electric power transmission systems multimachine very dynamic, i.e. systems that are experiencing rapid changes in the electrical load from time to time. Therefore, in this study was developed based on neuro-fuzzy method is applied to the adaptive UPFC for adaptively controlling the power flow in electric power transmission systems multimachine very dynamic. In this study, three phase fault is applied to the multimachine system. The results are taken to be consideration of PI and neuro-fuzzy controllers. The PI and neuro-fuzzy controllers show nearly same results but there is a low overshoot occurred during the fault in the neuro-fuzzy controllers results. According to results that UPFC improves the system performance under the transient and the normal conditions. However, it can control the power flow in the transmission line, effectively.